Optimalisasi Peran Dosen Wali melalui Pemanfaatan Microsoft Teams sebagai Media Komunikasi dan Konseling Akademik - Cyntia Lasmi Andesti; Ummul Fitri Afifah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
Academic advisors play a strategic role in supporting students' academic success and personal development. Unfortunately, this role has not been fully optimized due to limited communication tools, restricted meeting times, and the absence of an integrated mentoring system. Through this Community Service Program, efforts were made to enhance the role of academic advisors by utilizing Microsoft Teams as a medium for communication and academic counseling. The program focused on first-semester students from a study program at Politeknik Negeri Batam. All activities were conducted online, including the identification of student needs, mapping of academic and non-academic problems, as well as the implementation of mentoring sessions and follow-up actions. The results show that the use of Microsoft Teams improved the quality of interaction between academic advisors and students, strengthened students' self-confidence and independence, and fostered local leadership among them. In addition, there was a positive shift in communication patterns and a collective awareness of the importance of academic support networks. These findings indicate that a digital approach to academic mentoring is an effective, flexible, and sustainable strategy for building an active and supportive learning community.